2013
DOI: 10.1007/s40261-012-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Propiverine

Abstract: Propiverine is a well established antimuscarinic agent with a mixed mode of action in the treatment of symptoms associated with overactive bladder (OAB). As well as blocking muscarinic receptors in the detrusor muscle, the drug also inhibits cellular calcium influx, thereby diminishing muscle spasm. In patients with symptoms of OAB resulting from idiopathic detrusor overactivity (IDO) or neurogenic detrusor overactivity (NDO), propiverine demonstrated dose-dependent efficacy and tolerability, with adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Some studies demonstrated the superior tolerability of propiverine over oxybutynin, with comparable efficacy in children [ 74 , 86 – 88 ]. In children and adolescents with IDO or nDO, propiverine was generally more effective and better tolerated than oxybutynin and provides a valuable option for the treatment of DO [ 89 91 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Some studies demonstrated the superior tolerability of propiverine over oxybutynin, with comparable efficacy in children [ 74 , 86 – 88 ]. In children and adolescents with IDO or nDO, propiverine was generally more effective and better tolerated than oxybutynin and provides a valuable option for the treatment of DO [ 89 91 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…α‐Hydroxycarboxylic acids (α‐HCAs) are of keen interest for widespread applications in food, cosmetics, textiles, commodity chemicals, and polymer industries [3] . Additionally, α‐HCAs are ubiquitous in various pharmaceuticals and bioactive molecules [3b–e,h] . However, the current manufacturing approaches for synthesizing these molecules can hardly satisfy the market need [3a,b] .…”
Section: Introductionmentioning
confidence: 99%